Smart μLED Display-VLC System With a PD-Based/Camera-Based Receiver for NFC Applications - Xianbo Li; Babar Hussain; Jian Kang; Hoi Sing Kwok; C. Patrick Yue (IEEE Photonics Journal)
This paper presents a smart micro-light-emitting-diode (μLED) display system employing visible light communication (VLC) as the near-field communication technology for portable devices equipped with μLED displays. In the transmitter, a VLC modulator is integrated into a 400 × 240 gallium nitride (GaN) μLED display with a pixel size of 30 × 30 μm2 to enable simultaneous display and VLC functions. In the receiver, two different configurations are implemented, including a photodiode (PD)-based and a smartphone camera-based receiver. The smart μLED display-VLC system with the two different receivers is characterized by varying the distance and the angle between the transmitter and the receiver. Experimental results show that the PD-based system can achieve a bit rate of 2 Mb/s and a maximum overall data rate of 550 kb/s beyond 10 cm, but it is sensitive to angular misalignment. In contrast, the camera-based system is more suitable for the transmission of short pieces of information at a bit rate of 16.6 kb/s, and the maximum overall data rate is 5 kb/s at a distance of 5 cm (and 2.5 kb/s when the distance is extended to 10 cm). Moreover, the camera-based system is less sensitive to angular misalignment.